Changes in Blood Pressure Variability in Children with Postural Tachycardia Syndrome - Shuangshuang Gu; Shuo Wang; Yuwen Wang; Juan Zhang; Hong Cai; Runmei Zou; Cheng Wang (MDPI AG, 2023)
(1) Objective: In this research, we explored the difference in blood pressure variability (BPV) between children with postural tachycardia syndrome (POTS) and healthy children. Furthermore, we tried to investigate the effect of BPV on POTS and its relationship with prognosis of POTS. (2) Methods: 47 children with POTS (11.2 ± 1.8 years, 23 males) were enrolled in the POTS group and 30 healthy children (10.9 ± 1.9 years, 15 males) were matched for the control group. All participants completed 24 h ambulatory blood pressure monitoring (24hABPM). Thirty-three children with POTS were followed up for 52.0 (30.5, 90.5) days and were divided into a response group and a non-response group after evaluation. (3) Results: The 24 h diastolic blood pressure standard deviation (24hDSD), daytime diastolic blood pressure standard deviation (DDSD), nighttime systolic blood pressure standard deviation (NSSD), daytime diastolic blood pressure variation coefficient (DDCV) and nighttime systolic blood pressure variation coefficient (NSCV) in the control group were lower than those in the POTS group (p < 0.05). Percentage of females, age and height were lower in the response group than in the non-response group in children with POTS (p < 0.05). Univariate analysis showed that 24hDSD, DDSD, NSSD, DDCV and NSCV were potential risk factors for POTS, and sex and height were potential risk factors for poor prognosis of POTS. After adjusting for covariates, the risk of POTS increased by 48%, 53% and 49% when DDSD, NSSD and NSCV increased by 1 mmHg, 1 mmHg and 1%, respectively. The risk of poor prognosis in females was 12.99 times higher than that in males. (4) Conclusions: The results suggest that children with POTS may have an abnormal circadian rhythm in blood pressure and increased BPV. DDSD, NSSD and NSCV are independent risk factors for POTS, and being female is an independent risk factor for poor prognosis of POTS.